Coda: Autobiography in Anthropology, Then and Now. Issue 2 (1st September 2022) - Wulff, Helena
Abstract : Celebrating the thirtieth anniversary of the first publication of the volume Anthropology and Autobiography (1992) edited by Judith Okely and Helen Callaway, AJEC 31(1) features an inspiring special issue devoted to this topic, then and now. Starting from the beginning, we learn about the appalling resistance Judith Okely faced when she suggested Anthropology and Autobiography as a theme for the 1989 ASA (Association of Social Anthropologists of the UK) Conference. The idea to include the experience of the fieldworker, his or her emotional reactions, and issues related to gender, age and race – in the research and later even the use of "I" in the writing – came from the 'writing culture' movement in the United States. This early resistance against reflexivity and autobiography in British anthropology can be understood as a generational intolerance of American intellectual influence. As Ernest Gellner (1988: 26) suggested in a review of Clifford Geertz' Works and Lives : My own advice to anthropology departments is that this volume be kept in a locked cupboard, with the key in the possession of the head of department, and that students be lent it only when a strong case is made out by their tutors.